AVIFAUNA PADA TIGA TIPE HABITAT DI KEBUN RAYA BANUA, BANJARBARU, INDONESIA - Ali Yasin; Mochamad Arief Soendjoto; Eko Rini Indrayatie (Jurnal Sylva Scienteae, 2024)
There is no available and published data on the avifauna (birds) that inhabit the Banua Botanical Gardens, Banjarbaru. The research was carried out with the aim of identifying the birds in the botanical gardens, measuring species diversity, and comparing the similarities of bird communities to habitat types in the botanical gardens. Two observation plots were each placed on the type of habitat in the form of open land, mixed plants, and acacia vegetation. Birds were observed within an observation radius of 50 m in open land and 30 m in mixed plants and acacia vegetation with binocular assistance at 07.00-10.00 and 15.30-17.30 for 3 replications. Data in the form of bird species names and the number of individuals for 3 replications were processed in order to obtain the Shannon-Wienner species diversity index and Dice similarity index or its modification. Twenty-four of the 25 bird species were found in open fields, 23 in mixed crops, and 22 in acacia vegetation. The community similarity index ranged from 0.89 to 0.98 when calculated based on the presence of species or from 0.97 to 0.99 when based on the number of individuals. Based on the difference in the number of bird species which is only 1-2 between habitat types, the similarity index of bird communities between habitat types that is closer to 1, and also field conditions related to the area and location of the habitat type and the availability of bird food in those habitat types, habitat types are not qualitatively significant. In other words, in subsequent bird research, only one type of habitat should be considered in the Banua Botanical Gardens, especially since this botanical garden is still under construction in the next 10 yearsBelum ada data tersedia dan terpublikasi tentang avifauna (burung) yang menghuni Kebun Raya Banua, Banjarbaru. Penelitian dilaksanakan dengan tujuan mengidentifikasi burung di kebun raya itu serta mengukur keragaman spesies dan membandingkan kemiripan komunitas burung pada tipe-tipe habitat di kebun raya itu. Dua plot pengamatan masing-masing diletakkan pada tipe habitat yang berupa lahan terbuka, tanaman campuran, dan vegetasi akasia. Burung diamati dalam radius pengamatan 50 m pada lahan terbuka serta 30 m pada tanaman campuran dan vegetasi akasia diamati dengan bantuan binokuler pada jam 07.00- 10.00 dan 15.30-17.30 selama 3 kali ulangan. Data yang berupa nama spesies burung dan jumlah individu selama 3 kali ulangan diolah sehingga diperoleh indeks keragaman spesies Shannon-Wienner dan indeks kemiripan Dice atau modifikasinya. Dua puluh empat dari 25 spesies burung ditemukan di lahan terbuka, 23 di tanaman campuran, dan 22 di vegetasi akasia. Indeks kemiripan komunitas berkisar 0,89‒0,98 bila dihitung berdasarkan pada kehadiran spesies atau 0,97‒0,99 bila berdasarkan pada jumlah individu. Berdasarkan pada selisih jumlah spesies burung yang hanya 1-2 antara tipe habitat, indeks kemiripan komunitas burung antar-tipe habitat yang mendekati 1, dan juga kondisi lapangan terkait dengan luas dan letak tipe habitat serta ketersediaan makanan burung pada tipe habitat itu, tipe-tipe habitat secara kualitatif tidak berbeda signifikan. Dengan kalimat lain, dalam penelitian burung berikutnya, hanya satu tipe habitat saja yang sebaiknya dianggap ada di Kebun Raya Banua, apalagi kebun raya ini masih dalam pembangunan dalam 10 tahun ke depan